Emotional Regulation, Self-Compassion, Medication Adherence and Quality of Life in Dermatologic Patients - Anum Amjad, Iffat Batool, Nasreen Akhtar, Muhammad Zohaib Khan, Shah Rukh Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To investigate the relationship between emotional regulation, self-compassion, medication adherence, and quality of life in dermatologic patients. Method: The sample consisted of 150 young adults (males=51 (34%) and females=99 (66%)). The quantitative data was gathered via self-reported questionnaires including Emotion Regulation Questionnaire1, Neff’s Self-Compassion Scale (Short-Form)2, Medication Adherence Rating Scale3, Quality of Life Scale4, and a demographic information form. Results: Significant positive associations were explored among emotional regulation, self-compassion, and quality of life. In contrast, negative significant associations were found between self-compassion, medication adherence, and quality of life. The multiple regression analysis suggested a positive regression coefficient of self-compassion and a negative regression coefficient of medication adherence on the quality of life in dermatologic patients with a 41% variation. The results of the independent sample t-test specified non-significant gender differences in terms of emotional regulation, self-compassion, medication adherence, and quality of life in dermatologic patients. However, the significant difference was explored in the marital status (unmarried and married) in terms of i.e.,self-compassion, medication adherence, and quality of life. Conclusion and Implications: The study’s findings have contributed to the gap of literature in the domains of psychology, dermatology, and clinical studies in Pakistan. The result of the study would be helpful for psychologists and dermatologists to make plans for enhancing emotional regulation, self-compassion, medication adherence, and quality of life in dermatologic patients. Keywords: Emotional Regulation, Self-Compassion, Medication Adherence, Quality of Life, and Dermatologic Patients.